Golf destinations' brand personality: the case of the Algarve - Pereira, Rosária Luísa Gomes (2015)
The purpose of this research is to develop and validate a measurement scale to assess golf destinations’ brand personality and therefore to perceive the destination personality of the Algarve as a golf destination. Based on literature review on human personality, brand personality, destination brand image and marketing scales validation procedures, an initial 36 unrepeated items were the base for a survey instrument. Those items were generated from the literature, from the results of individual interviews with experts in tourism and golf in the Algarve and from promotional texts in golf- related websites. After content validation, the items were allocated into categories of attributes by a panel of expert judges. A survey was then applied to a convenient sample of 600 golf players in the Algarve, and 545 (valid) questionnaires were analysed to refine the scale. Golf players assessed the components of the relational brand personality (functional, symbolic and experiential) as well as the Algarve as a golf destination. A taxonomy of brand personality was developed and tested in the Algarve as it is recognized as one of the world best golf destination. The developed taxonomy of brand personality was assessed in two ways: 1) through the overall perception of the Algarve as a golf destination and 2) through the perception of specific attributes of the destination grouped into three main categories (functional, symbolic and experiential). Therefore, two multi-dimensional brand personality models were estimated by using structural equation modelling. Findings of this study indicate that golf players ascribe personality characteristics to destinations. The brand personality of the Algarve is translated into three main dimensions enjoyableness, distinctiveness and friendliness when tourists/golf players reveal their overall perception of the destination. The brand personality of golf destination Algarve is reflected in the dimensions reliability, hospitality, uniqueness and attractiveness when tourists assess the components of the relational brand personality. Refined scales consisting of 10 and 12 items were finally derived meeting both reliability and validity requirements. This study does not replicate Aaker’s (1997) personality dimensions and very little parallelism can be drawn with Aaker’s (1997) brand personality scale since only three items from her scale were validated in both models: friendly and cheerful, (sincerity), reliable (competence). The same is verified concerning the ‘Big-five’. The human personality traits (HPT) validated to describe golf destinations personality are only four helpful, pleasant (agreeableness), relaxed (emotional stability), and innovative (intellect or openness). As far as destination image descriptors (DID) are concerned, the items appealing, relaxed and safe were validated, while traits suggested by the interviews and website promotional texts such as calm, natural, spectacular, unique, welcoming, and the best (destination-specific traits) appear to be appropriate to describe the personality of a golf destination. The results suggest that the overall perception of the Algarve´s brand personality is described by the dimensions enjoyableness, distinctiveness and friendliness. Moreover, the relational perspective revealed that the functional attributes of the destination are described by the dimension reliablility, while the symbolic attributes are described by the dimensions hospitablility and uniqueness and finally its experiential attributes are described by the dimension attractiveness. These results show that a golf destination´s brand personality should not just be based on good golf practices. Theoretical and practical implications are discussed in the context of destination brand personality.